Relationship between Personal Hygiene During Menstruation With Events Pruri tus Vulvae For Young Women in Islamic Boarding Schools Malang Regency - Lailatul Erikatus Sholihah; Feriana Ira Handian; Sismala Harningtyas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Personal hygiene is an important factor in an effort to maintainhealth, this is done to avoid disease and can get used to living a healthier life.Most of us bellieve that hygiene problems are commonplace. The aim of thisstudy was to determine a significant rellationship between personal hygieneduring menstruation and the incidence of pruritus vulvae in young women atIslamic boarding schools in MalangObjectives: The sample in this study was 118 young womenMethods:The research design uses a cross-sectional approach. The sample inthis study was 118 young women using proportional random samplingtechnique. The instrument in this study was a personal hygiene questionnaireduring menstruation and pruritus vulvaeResults:The results of the study proved that most of the 65 (55.1%)respondents experienced sufficient personal hygiene and most of the 55(46.6%) respondents experienced moderate priuritus vulaeConclusions: Spearman rank test results show that there is a 2 correllationbetween personal hygiene during menstruation and the frequency of pruritusvulvae in young women at Islamic boarding schools in Malang Regency with asignificant value (p = 0.000) < (0.05), and a correllation coefficient of 0.500which means that both variables have moderate rellationship strength.Suggestions for the respondents of this study are expected to maximize thelevell of cleanliness and prevent symptoms of pruritus vulvae